Wilms’ Tumor 1-Associated Protein Contributes to Chemo-Resistance to Cisplatin Through the Wnt/β-Catenin Pathway in Endometrial Cancer - Xie, Wenli; Liu, Naifu; Wang, Xiangyu; Wei, Ling; Xie, Wenyan; Sheng, Xiugui (Frontiers in Oncology, 2021)
Background: Cisplatin remains the mainstay of endometrial cancer (EC) chemotherapy. Wilms’ tumor 1-associated protein (WTAP), playing a critical role in transcriptional and post-transcriptional regulation, has been reported as an oncogene, and its expression is elevated in multiple types of human tumors. Recent evidence has shown that the increased expression of WTAP is also closely related to chemo-resistance. However, its specific role in the susceptibility of human EC cells to cisplatin remains largely unexplored. Methods: WTAP over-expression and WTAP depletion cells lines as well as their corresponding controls were constructed by transfection with lentivirus. Western blotting analysis and quantitative real-time polymerase chain reaction (qRT-PCR) were employed to detect the expression of WTAP. Cell proliferation assay, colony formation assay, cell cycle assay and apoptosis analysis were adopted to evaluate the effect of WTAP on the chemo-sensitivity of EC cells to cisplatin as well as its underlying mechanism. Immunofluorescence staining was used to assess the translocation of β catenin. Moreover, subcutaneous xenograft tumor model was established to assess the effect of WTAP on tumor growth after cisplatin treatment. Results: Depletion of WTAP in RL95-2 cells significantly enhanced the chemo-susceptibility of cells to cisplatin and increased the cell apoptosis, while WTAP over-expression in ARK-2 cells exhibited the opposite effects. Additionally, WTAP depletion clearly suppressed xenograft-tumor growth and enhanced sensitivity and apoptosis of tumor cells in vivo. Mechanistic analysis exhibited that WTAP over-expression facilitated the cytoplasm-to-nucleus translocation of β catenin and enhanced the GSK3β phosphorylation at Ser9, while WTAP depletion revealed the opposite results, indicating that WTAP rendered chemo-resistance of EC cells to cisplatin by promoting the Wnt/β-catenin pathway. Conclusions: WTAP might promote the chemo-resistance of EC cells to cisplatin through activating the Wnt/β-catenin pathway. Collectively, our findings offered novel insights into EC treatment.